STUDIES ON THE LENGTH OF OVER HANG FOR TRAWLS - NAIR, R S; VERGHESE, C P; NAYAR, S GOPALAN; ABBAS, M SYED; KURIYAN, G K (Fishery Technology, 2025)
The effect of overhang and its optimum size on a bulged beUy type trawl net was studied and the results reported in this paper.